Inertial measurement unit based knee flexion strength-power test for sprinters - Nagahara, R.; Murata, M. (International Journal of Sports Science & Coaching, 2020)
This study aimed to examine whether sprinting performance would be associated with knee flexion strength-power capabilities measured using a recently developed inertial measurement unit (IMU) based system. Sixteen male sprinters performed 60-m sprints and the IMU based knee flexion strength-power test which consisted of five serial knee flexion-extension motions in three conditions (unweighted, 0.75 or 1.5 kg ankle weighted) for both legs. Spatiotemporal variables during sprinting for a 50-m distance were obtained using a long force platform system. The knee flexion joint kinetic variables during the knee flexion strength-power test were collected using one IMU. Running acceleration during the entire sprinting was positively correlated with the knee flexion positive work measured using the unweighted right knee flexion strength-power test (r = .521-.721). Moreover, step frequencies at the 13th-16th, 17th-20th and 21st-22nd step sections and during the entire sprint were positively correlated with the knee flexion positive work measured using the unweighted right knee flexion strength-power test (r = .506-.566), while step length did not show any correlations with the knee flexion strength-power test variables. The results demonstrate that the greater right knee flexion strength-power capabilities measured using IMU based method in the unweighted condition are advantageous for better sprinting performance through higher step frequency. The IMU-based knee flexion strength-power test in the right leg unweighted condition will likely be useful for physical fitness evaluation of sprinters on the field setting.